VEGF Promotes Proliferation of Human Glioblastoma Multiforme Stem-Like Cells through VEGF Receptor 2 - Chengshi Xu; Xing Wu; Jianhong Zhu (The Scientific World Journal)
Cancer stem-like cells, which have been described as tumor-initiating cells or tumor-propagating cells, play a crucial role in our fundamental understanding of glioblastoma multiforme (GBM) and its recurrence. GBM is a lethal cancer, characterized by florid vascularization and aberrantly elevated vascular endothelial growth factor (VEGF). VEGF promotes tumorigenesis and angiogenesis of human GBM stem-like cells (GBSCs). However, whether and how VEGF contributes to GBSCs proliferation remain largely uncertain. In this study, human GBSCs were isolated from surgical specimens of glioblastoma and cultured in medium favored for stem cell growth. Neural Colony-Forming Cell Assay and ATP assay were performed to measure GBSC proliferation under normoxia (20% O2) and hypoxia (1% O2). Our observations demonstrate that exogenous VEGF stimulates GBSC proliferation in a dose-dependent manner via VEGF Receptor 2 (VEGFR2); while VEGF Receptor 1 (VEGFR1) has a negative feedback effect on VEGFR2 when cells were exposed to higher concentration of VEGF. These results suggest that suppressing VEGFR2-dependent GBSC proliferation is a potentially therapeutic strategy in GBM.